Supplemental Teaching: A Learning Model to Teach English for Professionals in Economic Education - Subari, Imam; Herlisya, Destia; Marcela, Eny Dwi; Sutiyono, Akhmad (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study was to improve the English language skills of fourth semester students majoring in economic education for the 2021/2022 academic year at STKIP PGRI Bandar Lampung. The problem raised in this study is whether the use of the supplemental teaching method can improve English language skills and student motivation. The method in this study used a classroom action research design which was carried out in three cycles. The results of the study can be concluded as follows: first, the increase can be seen from the average score of 58.93 in the first cycle, to 67.6 in the second cycle, and increased to 86.70 in the third cycle. The increase in the average value that occurred was 19.2%. Second, increasing students' ability in English is also followed by changes in student learning behaviour in a positive direction. Students become happier, more active, and give a positive response to learning English.